Happy Healthy Homes: Content Analysis of Intervention Delivery and Participant Feedback. (29th May 2020) - Williams, Bethany; Sisson, Susan; Bhattacharya, Sukanya; Merchant, Cady; Slawinski, Megan; Salvatore, Alicia
Abstract: Objectives: Describe intervention delivery and participant feedback for Happy Healthy Homes, a pilot interdisciplinary study to improve health environments for family childcare homes (FCCHs), a unique and understudied childcare setting. Methods: Providers received continuing education focused on either (1) enhancing quality of the nutrition environment, self-efficacy, and practices or (2) improving providers' environmental health (ECO) literacy, self-efficacy and practices. Detailed written post-intervention logs were completed following educational sessions. Content analysis was performed to summarize information on participant goals and challenges. Results: Participants included 46 FCCH providers (25 nutrition, 21 environmental health, 100% female). Common nutrition goals related to family-style meal service (77%), and common ECO goals included increased use of microfiber (69%). The most prevalent challenges to meeting nutrition goals included catering to a varying composition/dynamic of children (50%) and having a lack of time (19%). The most prevalent challenges meeting ECO goals included a lack of time (47%) and parent and/or child resistance to practices (21%). Interventionist-reported challenges to delivery included having children or other potential distractions present during session (25%), providers' tendencies to pull discussion off-topic (22%) and pressure from a strict time constraint or scheduling issue (20%). Conclusions: Future intervention delivery in FCCHs should continue to promote goal-setting autonomy and provide resources to support implementation of best practices. However, efforts could improve by tailoring to multiple age groups, allowing ample time for discussion, and utilizing regular reminder calls/texts to avoid scheduling confusion. Funding Sources: This study is supported by the Agriculture and Food Research Initiative grant from the USDA National Institute of Food and Agriculture and the National Institute of General Medical Sciences award.